Communicating supranational governance? The salience of EU affairs in the German Bundestag, 1991–2013 - Christian Rauh (European Union Politics, 2015)
Against democratic deficits of European Union (EU) governance, recent literature emphasizes the communicative function of national parliaments. Yet, arguments from the broader EU politicization literature have been only rarely applied to public parliamentary debates. This article integrates arguments about supranational authority and partisan competition as key drivers of debates on the EU and tests respective implications by an automated text analysis that retrieves EU references in all 1,393 plenary debates of the German Bundestag during 1991–2013. A panel analysis identifies authority transfers as the strongest predictor for EU salience in the plenary. EU references furthermore increase with supranational policy output, public EU visibility, and a differentiating public opinion. With regard to partisan emphasis, mainstream and particularly governing parties push European issues in the German Bundestag.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; European integration; national parliaments; politicization; salience; text analysis